Performance Analysis of Proactive Routing Protocol Based on Different Network Load in Mobile Ad-Hoc Network (MANET) - Zulkifli, Che Zalina; Ismail, Roswan; Ibrahim, Abu Bakar; Mashoedah; Boonsong, Wasana (Evolution of Information, Communication and Computing System, 2022)
Mobile Ad hoc Network (MANET) is a collection of wireless mobile nodes that dynamically form a network temporarily without any support of central administration. Moreover, every node in MANET moves arbitrarily making the multi-hop network topology to change randomly at unpredictable times. Therefore, the routing protocol that able to cope with the dynamic nature of the MANET is needed to maintain the communication data between mobile nodes in the network. This paper presents the performance comparison of OLSR and DSDV, protocols based on metrics such as packet delivery ratio, average end-to-end delay, and routing overhead by using the NS-2 simulator. The simulation results show that the performance of DSDV outperformed OLSR protocols in terms of average delay and routing overhead.